Os efeitos do pró-letramento na formação das professoras alfabetizadoras do município de Conselheiro Lafaiete - Lucimara de São José (2012)
This work intends to analyze the effects of Pró-Letramento (Pro-Literacy) - Program of Continuing Education, implemented since 2005 by the Federal Government in the public schools - to the practices of literacy teachers who work in the first years of elementary school. This qualitative research was developed primarily through the collection and analysis of reports obtained from semi-structured interviews carried out with the tutor responsible for the course of Literacy and Language of the Pró-Letramento (Pro-Literacy) and ten participants teachers of the training program, implemented between October 2008 and December 2010 in Conselheiro Lafaiete (MG). We also performed the study of materials that organize and guide the implementation of the Pró-Letramento (Pro-Literacy), such as the General Guide of the Program, the Fascicles of guidance for tutors and the didactic collection of the area of language destined for course participants. Besides the interviews and documentary analysis, we used as procedure for data collection questionnaires, answered by the research subjects in the initial phase of its development. In order to deepen the analysis on the effects of Pró-Letramento (Pro-Literacy) in the practices of teachers, we chose to study in one of the chapters of the dissertation, the possible relations between developed evaluation practices in the classroom and what is proposed by the Training Program. Data produced by the survey showed that some of the conditions of implementation and development of the actions of formation present at this town in Minas Gerais, influenced significantly the implementation of the Program, contributing to the realization of a fragmented training model, different from the one proposed by the public policy. It was indicated, therefore, the importance of local management of continued education policies that are developed nationally. Regarding the effects of the program in the practices of teachers, we identified three particular situations that characterize the types of appropriations that teachers made from the training course. The first refers to changes made in work of teachers due to the experience of social practices of literary reading, organized in the meetings of the course on Literacy and Language. The reports showed a greater investment of the teachers in proposing activities of reading literary texts in the classroom because of the experience lived during the course. The second concerns the more general contributions, which are not explicitly named by the teachers, offered by the course due to the exchange of experiences and interaction between the participants subjects of the training. The third indicates effects associated with the content of one of volumes of the didactic collection of the "Pró-Letramento" (Pro-Literacy). The teachers stressed in their statements the relevance of the fascicle that deals with the diagnostic assessment of literacy for their training. Teachers indicated the use of this material in their evaluation practices and expressed their importance, relating it to the external context of systemic assessments of literacy proposed by the Federal and State governments. The work allows us to infer, first, that the acquisition of knowledge that teachers perform from training courses is realized in articulation with the consolidated knowledge and validated by them in their professional practices. Secondly, the educational content available on the actions of training, when incorporated by teachers, are transformed and reinterpreted in order to meet the demands identified in the school routine. Overall, the results show that it is the pragmatic approach that defines and directs the appropriations of contents held by teachers.